Body Size and Ectoparasitic Infestations in the Mediterranean Pond Turtle Mauremys leprosa (Testudines, Geoemydidae) in Majen Belahriti Pond (North-Eastern Algeria) - Ramdani, K.; Ziane, N.; Younsi , M.; Ben Krinah, C.; Bouchahdane, I.; Rouag, R. (Publishing House "Akademperiodyka" of the National Academy of Sciences of Ukraine, 2024)
Morphological parameters were measured on a population of the Mediterranean pond turtle Mauremys leprosa (Schweigger, 1812) in Majen Belahriti pond in the region of Guelma (North-east of Algeria). Females exhibited a longer carapace length (CL) at 177 ± 23.85 mm, surpassing that of males (151.45 ± 31.12 mm), and they also displayed a higher body weight (BW) at 756.52 ± 243.91 g, which was notably greater than that of males (453.09 ± 224.42 g). Placobdella nabeulensis Ben Ahmed, Gajda, Utevsky, Kwist & Świątek, 2023 (Hirudinida, Glossiphoniidae) was identified as the only ectoparasite affecting M. leprosa, with an average body length and width of 11 ± 5.83 mm and 5.1 ± 2.89 mm respectively. The intensity, represented by the average number of leeches per turtle, was calculated to be 2.21 ± 1.31 for this specific population and a prevalence rate of 21.17 %. The tail region showed the highest parasite load, indicating its increased susceptibility compared to other body parts.